Induced breeding of oranda goldfish (Carassius auratus) by using ovafish - Sylliang, Shanborlang D.; Sangma, Balkam R; Vyas, Vipin (AG Volumes, 2025)
The present study investigated the induced breeding of Oranda goldfish (Carassius auratus) using Ovafish hormone under controlled conditions at the Meghalaya State Fisheries Research and Training Institute (MSFRTI), Mawpun, Meghalaya, from July to December 2023. Brooders were conditioned for 25 days in disinfected and pre-prepared tanks, and fed a high-protein diet comprising bloodworms and TetraBits. Physico-chemical parameters of both brood and breeding tanks were closely monitored, maintaining optimal ranges for temperature (28–31°C in brood tanks; 20–26°C in breeding tanks), dissolved oxygen (5–6 ppm), pH (7.3–7.6), alkalinity (140–200 mg/L), and hardness (100–120 mg/L). Hormonal induction was carried out using Ovafish at dosages of 0.5 ml/kg for females and 0.2 ml/kg for males. The treatment resulted in a significantly higher fertilization and hatching success rate ( 93%) compared to natural breeding ( 65%). Fertilized eggs were identified by their transparent shells with grey or black spots, while unfertilized eggs appeared opaque. The study concludes that Ovafish is effective in enhancing reproductive success in C. auratus, suggesting its potential application in ornamental fish hatcheries to improve breeding efficiency.